Digitizing radiology films using flat-bed scanner and produce a multimedia digital teaching file in musculoskeletal radiology - Shuaib, I. L.; Alias, N. A.; Muhamah, M.
Digital images have been long established in radiology department. Despite this, most radiology teaching films has been film-based. The drawback of this conventional system is that it consumed space, only one user can use at any one time and expensive. Analogue radiology films were digitized using flatbed scanner with transparency adaptor and digital camera. Digital-based teaching files using personal computer (PC) should be encouraged as this will reduce space for storing, can be distributed without much cost, inexpensive, many users can use at the same time and others can use even though at different place using the internet. The teaching file was prepared using HyperText Mark-up Language (HTML) as this can be used using any web browser. It is now available in University Sains Malaysia, Kelantan Campus Branch (USMKCK) intranet.